Labour Before the Law : The Regulation of Workers' Collective Action in Canada, 1900-1948 - Fudge, Judy; Tucker, Eric, 1951- (Book collections on Project MUSE., 2004)
In this groundbreaking study of the relations between workers and the state, Judy Fudge and Eric Tucker examine the legal regulation of workers' collective action from 1900 to 1948. They analyze the strikes, violent confrontations, lockouts, union organizing drives, legislative initiatives, and major judicial decisions that transformed the labour relations regime of liberal voluntarism, which prevailed in the later part of the nineteenth century, into industrial voluntarism, whose centrepiece was Mackenzie King's Industrial Disputes Investigation Act of 1907. This period was marked by coercion and compromise, as workers organized and fought to extend their rights against the profit oriented owners of capital, while the state struggled to define a labour regime that contained industrial conflict. The authors then trace the conflicts that eventually produced the industrial pluralism that Canadians have known in more recent years.By 1948 a detailed set of legal rules and procedures had evolved and achieved a hegemonic status that no prior legal regime had even approached. This regime has become so central to our everyday thinking about labour relations that one might be forgiven for thinking that everything that came earlier was, truly, before the law. But, as Labour Before the Law demonstrates, workers who acted collectively prior to 1948 often found themselves before the law, whether appearing before a magistrate charged with causing a disturbance, facing a superior court judge to oppose an injunction, or in front of a board appointed pursuant to a statutory scheme that was investigating a labour dispute and making recommendations for its resolution.The book is simultaneously a history of law, aspects of the state, trade unions and labouring people, and their interaction within the broad and shifting terrain of political economy. The authors are attentive to regional differences and sectoral divergences, and they attempt to address the fragmentation of class experience.